Творчість Т. Г. Шевченка в дослідженнях Б. В. Якубського - Радько, Антоніна; Radko, Antonina (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті проаналізовано шевченкознавчі праці Б. Якубського, виокремлено основні питання, що входили до сфери його дослідницьких інтересів у цій галузі. Представлені праці не тільки вводяться до наукового обігу, а й заповнюють прогалини у бібліографуванні матеріалів про життя й творчість Т. Шевченка. The article is about the research of Shevchenko’s works made by Ukrainian specialist in literature B. Yakubsky, who worked in 20−30s of the 20th century. Major problems concerning the sphere of his research interests are pointed out and analyzed. The investigation of Shevchenko’s poetics is defined as a direction of primary importance in the works of the scholar. B. Yakubsky analyzed metrics, rhythmics, sound harmony and versification of «Kobzar», he was the first in Ukrainian history of literature, who used statistic method of analyzing poetry. The author also estimated the study of Shevchenko’s works in 1920s, paid attention to institutional problems of its development and appealed to bibliographic-statistic aspect, having analyzed Shevchenko’s scientific works in details. Presented and analyzed works of Yakubsky become a part of the scientific circulation as well as fill in gaps in bibliographic materials about T. Shevchenko’s life and work.
T. G. Shevchenko’s works in B. V. Yakubsky’s researches
Keywords: шевченкознавство; видання; поетика; метод; вірш; study of Shevchenko’s works; edition (issue); poetics; method; verse